Ukuran Perusahaan, Profitabilitas, Leverage, dan Likuiditas terhadap Nilai Perusahaan Manufaktur Sektor Industri Konsumsi yang Terdaftar di BEI - Jennifer Anggawinata; Rosita Chanaka; Suwarmansyah Suwarmansyah; Kelly Kwanty; Sauh Hweeh Teng (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study was to analyze the effect of firm size, profitability, leverage and liquidity on firm value. This research method is descriptive quantitative. The population used in this study is all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2018-2020, the sample selected by purposive sampling technique and obtained as many as 25 samples of companies. Researchers used secondary data and tested using multiple linear regression methods. The results showed, based on the results of the T test, it was found that, a) the firm size variable has a tcount value of 1.561, with a sig value of 0.123, and a tcount value < ttable which is 1.561<1.994; b) the profitability variable has a tcount value of 7.062, with a sig value of 0.000, and a tcount > ttable value which is 7.062>1.994; c) Leverage variable has a value of tcount with a value of -0.524, with a sig value of 0.602, and a value of -tcount > -ttable which is -0.524>-1.994; d) Liquidity variable has a tcount value of -2,351, with a sig value of 0.022, and a tcount> ttable value of -2,353>1,994. In conclusion, firm size has no effect on firm value, profitability has no effect on firm value, Leverage has no effect on firm value and liquidity has no effect on firm value. Keywords: Leverage, Liquidity, Firm Value, Profitability, Firm Size